Effects of central administration of the human Tau proteinon the Bdnf, Trkb, p75, Mapt, Bax and Bcl-2 genes expression in the mouse brain - A. S. Oreshko; A. Ya. Rodnyy; D. V. Bazovkina; V. S. Naumenko (Вавиловский журнал генетики и селекции)
Alzheimer’s disease is the most common form of dementia, affecting millions of people worldwide. Despite intensive work by many researchers, the mechanisms underlying Alzheimer’s disease development have not yet been elucidated. Recently, more studies have been directed to the investigation of the processes leading to the formation of neurofibrillary tangles consisting of hyperphosphorylated microtubule-associated Tau proteins. Pathological aggregation of this protein leads to the development of neurodegeneration associated with impaired neurogenesis and apoptosis. In the present study, the effects of central administration of aggregating human Tau protein on the expression of the Bdnf, Ntrk2, Ngfr, Mapt, Bax and Bcl-2 genes in the brain of C57Bl/6J mice were explored. It was found that five days after administration of the protein into the fourth lateral ventricle, significant changes occurred in the expression of the genes involved in apoptosis and neurogenesis regulation, e. g., a notable decrease in the mRNA level of the gene encoding the most important neurotrophic factor BDNF (brain-derived neurotrophic factor) was observed in the frontal cortex which could play an important role in neurodegeneration caused by pathological Tau protein aggregation. Central administration of the Tau protein did not affect the expression of the Ntrk2, Ngfr, Mapt, Bax and Bcl-2 genes in the frontal cortex and hippocampus. Concurrently, a significant decrease in the expression of the Mapt gene encoding endogenous mouse Tau protein was found in the cerebellum. However, no changes in the level or phosphorylation of the endogenous Tau protein were observed. Thus, central administration of aggregating human Tau protein decreases the expression of the Bdnf gene in the frontal cortex and the Mapt gene encoding endogenous mouse Tau protein in the cerebellum of C57Bl/6J mice.